2015
DOI: 10.1111/brv.12193
|View full text |Cite
|
Sign up to set email alerts
|

Natural disturbance impacts on ecosystem services and biodiversity in temperate and boreal forests

Abstract: In many parts of the world forest disturbance regimes have intensified recently, and future climatic changes are expected to amplify this development further in the coming decades. These changes are increasingly challenging the main objectives of forest ecosystem management, which are to provide ecosystem services sustainably to society and maintain the biological diversity of forests. Yet a comprehensive understanding of how disturbances affect these primary goals of ecosystem management is still lacking. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
381
2
7

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 594 publications
(401 citation statements)
references
References 494 publications
11
381
2
7
Order By: Relevance
“…D.A.M. The slide to which you refer contained a global map depicting the geographical distribution of papers addressing the impacts of fire, wind and bark beetles on ecosystem services and biodiversity ( [96], figure 1). Less than 1% of fire research identified by the authors had been conducted in Africa.…”
Section: Meeting Discussionmentioning
confidence: 99%
“…D.A.M. The slide to which you refer contained a global map depicting the geographical distribution of papers addressing the impacts of fire, wind and bark beetles on ecosystem services and biodiversity ( [96], figure 1). Less than 1% of fire research identified by the authors had been conducted in Africa.…”
Section: Meeting Discussionmentioning
confidence: 99%
“…The maintenance of a natural fire regime is often required to sustain or even enhance the productivity of ecosystems that have coexisted, or even coevolved, with a specific fire regime (Brockway et al 2002). Therefore, the impact of fire on a forest and its associated ecosystem services can be either positive or negative, depending on the forest type, the fire regime, and the ecosystem services (Thom and Seidl 2016).…”
Section: Fire Regulation and Mitigationmentioning
confidence: 99%
“…At the same time, a higher susceptibility of forests to disturbance has been interpreted as a consequence of past land use (Seidl et al 2009). However, recent large-scale dieback in remote natural forests, even at the alpine treeline, confirms the complexity and still rather limited knowledge of the interactions among disturbances, climate and land-use changes that seriously affect ecosystem functions and services (Dale 1997, Thom & Seidl 2016. The emerging conflict between increasing demands and a compromised or limited ES capacity is one of the key challenges for forest management and protection.…”
mentioning
confidence: 99%